060 Calcitonin gene-related peptide monoclonal antibody treats headache in patients with active idiopathic intracranial hypertension. Issue 6 (27th May 2022) - Yiangou, Andreas; Mitchell, James; Vijay, Vivek; Grech, Olivia; Bilton, Edward; Lavery, Gareth; Fisher, Claire; Edwards, Julie; Mollan, Susan; Sinclair, Alexandra
Abstract : Background: Headache is the dominant factor for quality of life related disability in idiopathic intracranial hypertension (IIH) and typically has migraine-like characteristics. There are currently no evidence-based therapeutics for headache in IIH, and consequently this is an important unmet clinical need. Case series: We report a series of seven patients in whom headaches were the presenting feature of IIH the headaches had migraine-like characteristics, as is typical in many IIH patients. Papilloedema settled (ocular remission) but headaches continued. These headaches responded markedly to erenumab, a monoclonal antibody targeted against the calcitonin gene related peptide (CGRP) receptor. Of note, there was a recurrence of raised ICP, as evidenced by a return of the papilloedema, however the headaches did not recur whilst treated with erenumab. Conclusions: Those with prior IIH who have their headaches successfully treated with CGRP therapy, should remain under close ocular surveillance (particularly when weight gain is evident) as papilloedema can re-occur in the absence of headache. These cases may suggest that CGRP could be a mechanistic driver for headache in patients with active IIH. a.yiangou@bham.ac.uk|NIHR Bursary 55